<span>B.When x=-4, y=-9 and when x=2, y=3.
</span><span>3y-6x=-3
3(-9) - 6(-4)= -3
-27 +24 =-3
-3 = -3
</span>
<span>3y-6x=-3
3(3) -6 (2) = -3
9 - 12 = -3
-3 = -3
</span>
Answer:
A = 2.1 ft^2
Step-by-step explanation:
The area of a triangle is
A = 1/2 bh where b is the base and h is the height
A = 1/2 ( 2.8)(1.5)
A = 2.1 ft^2
Answer:
Step-by-step explanation:
Vertex A of the triangle ABC when rotated by 90° counterclockwise about the origin,
Rule to be followed,
A(x, y) → P(-y, x)
Therefore, A(1, 1) → P(-1, 1)
Similarly, B(3, 2) → Q(-2, 3)
C(2, 5) → R(-5, 2)
Triangle given in second quadrant will be the triangle PQR.
If the point P of triangle PQR is reflected across a line y = x,
Rule to be followed,
P(x, y) → X(y, x)
P(-1, 1) → X(1, -1)
Similarly, Q(-2, 3) → Y(3, -2)
R(-5, 2) → Z(2, -5)
Therefore, triangle given in fourth quadrant is triangle XYZ.
Answer:
275/6
Step-by-step explanation:
The Newton`s law of cooling:
T = R + ( To - R ) * e ^(-kt )
We know that: T = 32° F ( the water freezes at 32° F ), To = 55° F, R = 5° F
and the cooling rate is: k = 0.012.
33° F = 5° F + ( 55° F - 5° F ) · 2.72^(-0.012 t )
33 - 5 = 50 · 2.72^(-0.012 t)
27 = 50 · 2.72^(-0.012 t)
2.72^(-0.012 t) = 27/50
1 / 2.72^(0.012 t) = 0.54
2.72^( 0.012 t ) = 1 : 0.54 = 1.85
0.012 t = log(base e) 1.85 = ln 1.85 = 0.6
t = 0.6 : 0.012 = 50
Answer: It would take 50 minutes.